Mother on Mothers Maternal Readings of Popular Television - Feasey, Rebecca (Peter Lang International Academic Publishing Group, 2015)
From Supernanny to Gilmore Girls, from Katie Price to Holly Willoughby, a wide range of examples of mothers and motherhood appear on television today. Drawing on questionnaires completed by mothers across the UK, this book sheds new light on the diverse ways in which mothers make sense of popular representations of motherhood on television.